(untitled) (EAAE Annual Conference Proceedings, 2023)
This research experience was developed in the frame of an “idea consultation” involving 20 Italian schools of architecture and aiming at the renovation of 18 existing educational complexes in the city of Mantua. Our research group designed a complex consisting of primary school, kindergarten and nursery school, conceived as an urban ecosystem interacting with the multi-ethnic community characterizing the Lunetta neighborhood. The proposed permeable linear system multiplies the different active environments available to the school and neighborhood communities in order to involve local people and promote social interaction.